Incidence and pattern of infections in pregnant women with bad obstetric history - Goud, N. Swetha; Reddy, M. Manasa; Desai, Savitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Adverse outcomes have been seen in pregnant women who had prior bad obstetric history along with infection with TORCH [toxoplasma, other infections (syphilis, varicella zoster, hepatitis B), rubella, cytomegalovirus, herpes simplex]complex and bacterial vaginosis. These infections are known to affect the health of the fetus. Objective was to study incidence and pattern of infections in pregnant women with bad obstetric history. Methods: A total of 190 patients with bad obstetric history fulfilling the methodology criteria were evaluated. Serological and molecular evaluations were carried out for TORCH complex and bacterial vaginosis was detected by both gram stain and gold standard clinical Amsel criteria and outcomes were followed. Results: Out of 190 pregnant women with bad obstetric history, a total of 36 (18.8%) were detected to have infections causing bad obstetric history. Toxoplasma was positive in 7 (20%) of the cases, 3 (51.92%) of them had abortions. Rubella in 12 (32%) of the cases, 7 (60%) cases had sensorineural deafness. Cytomegalovirus in 1 (2%) of the cases, 1 (100%) of the case had microcephaly. Herpes in 8 (22%) cases, 6 (71.1%) cases had abortions. Bacterial vaginosis in 8 (22%) of the cases, 4 (48.6%) cases had preterm delivery. The presence of infections with TORCH complex and bacterial vaginosis was related to adverse pregnancy outcomes. Conclusions: Women with bad obstetric history are prone to infections during pregnancy and have been found out to be associated with adverse pregnancy outcomes. Hence pregnant women should be screened so that early diagnosis and treatment of infections can be done to have better pregnancy outcomes.